Controversial issues in the management of hyperprolactinemia and prolactinomas - An overview by the Neuroendocrinology Department of the Brazilian Society of Endocrinology and Metabolism - Vilar, Lucio (2018)
Prolactinomas are the most common pituitary adenomas (approximately 40% of cases), and they represent an important cause of hypogonadism and infertility in both sexes. The magnitude of prolactin (PRL) elevation can be useful in determining the etiology of hyperprolactinemia. Indeed, PRL levels > 250 ng/mL are highly suggestive of the presence of a prolactinoma. In contrast, most patients with stalk dysfunction, drug-induced hyperprolactinemia or systemic diseases present with PRL levels < 100 ng/mL. However, exceptions to these rules are not rare. On the other hand, among patients with macroprolactinomas (MACs), artificially low PRL levels may result from the so-called "hook effect". Patients harboring cystic MACs may also present with a mild PRL elevation. The screening for macroprolactin is mostly indicated for asymptomatic patients and those with apparent idiopathic hyperprolactinemia. Dopamine agonists (DAs) are the treatment of choice for prolactinomas, particularly cabergoline, which is more effective and better tolerated than bromocriptine. After 2 years of successful treatment, DA withdrawal should be considered in all cases of microprolactinomas and in selected cases of MACs. In this publication, the goal of the Neuroendocrinology Department of the Brazilian Society of Endocrinology and Metabolism (SBEM) is to provide a review of the diagnosis and treatment of hyperprolactinemia and prolactinomas, emphasizing controversial issues regarding these topics. This review is based on data published in the literature and the authors' experience.